2016
DOI: 10.1021/acs.jpcc.6b01851
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Transport of Water and Ions Through a Carbon Nanotube: The Role of Ionic Condition

Abstract: Control of water and ion transport through nanochannels is of primary importance for the design of novel nanofluidic devices. In this work, we use molecular dynamics simulations to systematically analyze the coupling transport of water and ions through a carbon nanotube in electric fields. We focus on the role of ionic conditions, including the salt species and concentration, which can significantly regulate the ion and further the water transport. We find that the coupling of water–anions is stronger than wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
67
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 49 publications
10
67
1
Order By: Relevance
“…Certain aspects of such pores can be effectively mimicked by simple non-biological structures, for example graphene nanopores and metal-organic structures (2). Carbon nanotubes (CNTs) are also particularly attractive as structural templates because they can imitate many fundamental aspects of such pores including high transport efficiency, tunable pore diameters, functionalization, and well-defined hydrophobic interiors (45)(46)(47)(48)(49)(50). The relevant properties of CNT nanopores have been extensively studied, both experimentally and with simulations (49,(51)(52)(53).…”
Section: It Has Been Suggested Bymentioning
confidence: 99%
“…Certain aspects of such pores can be effectively mimicked by simple non-biological structures, for example graphene nanopores and metal-organic structures (2). Carbon nanotubes (CNTs) are also particularly attractive as structural templates because they can imitate many fundamental aspects of such pores including high transport efficiency, tunable pore diameters, functionalization, and well-defined hydrophobic interiors (45)(46)(47)(48)(49)(50). The relevant properties of CNT nanopores have been extensively studied, both experimentally and with simulations (49,(51)(52)(53).…”
Section: It Has Been Suggested Bymentioning
confidence: 99%
“…However, these films contain a disordered structure and the nanopores or sub-nanopores formed in those membranes for the transportation of water molecules and ions are not uniform. [3][4][5][6][7][8][9][10][11][12] Hence, materials that contain nanopores or sub-nanopores with uniform sizes, such as carbon nanotubes (CNTs) [13][14][15][16][17][18][19][20] and polymerized liquid crystals, [21][22][23][24][25][26][27][28][29] have attracted a great deal of interest as candidates for efficient water treatment membranes. It is expected that the alignment of pores, which is required for high water permeability, will be easier for polymerized liquid crystals than for CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…These features of LC membranes are not seen in hard materials that have been considered for use as water treatment materials, such as zeolite [30][31][32] and CNTs. [13][14][15][16][17][18][19][20] Elucidating how each of these features affects the permeability of water molecules and ions in sub-nano channels will contribute greatly to elucidating the factors that determine the water treatment performance.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Additionally, Su and Huang have recently shown that water and ions transport through the CNT frameworks are strongly coupled. [12,13] 2D nanoporous materials such as graphene with artificial nanometric holes (diameter of 10 Å or less) [14,15] have also been considered and several groups have reported improvement of both water transport and ionic selectivity through nanoporous graphene, [14][15][16][17][18] graphyne, [19,20] MoS 2 , [21][22][23] C 2 N [24] monolayers, and theoretical supersquare [25] materials. In a recent work, Garnier et al have shown that water permeation through subnanoporous boron nitride (sNBN) monolayers could even be faster than through nanoporous graphene, thus heralding boron nitride as a potential candidate for the next generation of nanofilters.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Additionally, Su and Huang have recently shown that water and ions transport through the CNT frameworks are strongly coupled. [ 12,13 ] 2D nanoporous materials such as graphene with artificial nanometric holes (diameter of 10 Å or less) [ 14,15 ] have also been considered and several groups have reported improvement of both water transport and ionic selectivity through nanoporous graphene, [ 14–18 ] graphyne, [ 19,20 ] MoS 2 , [ 21–23 ] C 2 N [ 24 ] monolayers, and theoretical supersquare [ 25 ] materials. In a recent work, Garnier et al.…”
Section: Introductionmentioning
confidence: 99%